Implikasi Komunikasi, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Stasiun PT. MRT JAKARTA - Muchsin, Muchsin; Zaharuddin, Zaharuddin; Hanaffy, Jamal (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The findings of this study on employee performance indicate that performance is still below optimal, and this is characterized by the existence of certain employees who are less capable of anticipating the risks that arise in the Station Staff Officer. Communication, motivation, and the work environment are just a few of the many elements that contribute to better or enhanced performance. It will be easy to achieve the desired employee performance if these factors are properly implemented; if not, the employee's performance will suffer and the company may experience additional human resource issues. This study sought to ascertain the direct and indirect relationships among work, motivation, and communication. The impact of the work environment at PT. MRT Jakarta station. In order to determine how to analyze the direct and indirect effects between exogenous and endogenous variables, this study employs a quantitative associative approach. The analysis path test is used to test the hypothesis. Determining the direct and indirect effects between exogenous and endogenous variables is the goal of the path analysis test. 42 saturated samples were used as the sampling strategy in this investigation. All of the workers in the Station Staff Officer units at Station PT. MRT Jakarta made up the study's sample. The findings of this study, which also used a path analysis test, show that communication has a direct and significant impact on motivation, that the work environment has a significant and significant impact on motivation, that communication has no significant impact on performance, and that motivation has a significant and significant impact on performance on units, including station staff officers at Station PT. MRT Jakarta. The findings of this study, which used a path analysis test, reveal the indirect effect that shows that, among station staff officers at Station PT. MRT Jakarta, communication influences performance through motivation and the work environment influences performance through motivation. According to the findings, the indirect effect has a greater impact on endogenous variables than the direct effect.